Financial constraints and cash holdings: Evidences from Chinese listed companies - Yan, Xi (2018)
This study seeks to analyse and examine the adjustments of corporate cash holdings from the aspect of financial constraints, aiming to solve the question that what the main determinants of the adjustments of corporate cash holdings are. The empirical evidence finds that the market friction caused by information asymmetry and other factors has an important influence on the financial behaviour of the company. Reducing the market friction between the company and the financial market is of great importance to improve the efficiency of external financing and reduce unnecessary cash savings. It also finds the positive correlation between the change direction of external financing transaction costs and the change direction of cash holdings and confirms our theoretical judgment. However, the dividend payment and cash holding do not have statistical relevance.